Simulation of the influence of aerosol particle characteristics on clouds and precipitation with LM-SPECS: Model description and first results - Grützun, V.; Knoth, O.; Simmel, M. (Atmospheric research, 2008)
The novel model system LM-SPECS is presented combining a spectral bin microphysics scheme and the three-dimensional Lokalmodell (LM, today called COSMO) of the German Weather Service (“Deutscher Wetterdienst”). The model is designed to investigate in detail the interaction of atmospheric aerosol particles, clouds and precipitation. The microphysics scheme includes a combined spectrum of wetted aerosols, cloud droplets and rain drops. As a first application of the model, sensitivity studies on an artificial deep convective cloud were done. The results produced by LM-SPECS are satisfying. The studies show, e.g., that a diminished initial particle number leads to larger cloud droplets and thus to a higher efficiency of coalescence. This results in a larger amount of precipitation. Furthermore, studies on mixed phase clouds show the influence of varying ice nuclei, such as bacteria, kaolinite and soot, on cloud properties. Here, a more effective freezing leads to an increased number of ice particles with smaller radii. The results point to the importance of a detailed knowledge of the underlying microphysical processes in order to understand the formation of clouds and precipitation more accurately. Though to date the model was applied to artificial cases only, the use of the mesoscale weather model allows for more complex realistic cases which are subject to further studies.